Peran Kearifan Lokal Sebagai Instrumen Pembangunan Ekonomi Desa: Studi Kasus Implementasi Program Pemberdayaan Masyarakat Berbasis Pariwisata - Adi Shambono; Khomsahrial Romli; M. Mawardi J; Sri Ilham Nasution (Universitas Veteran Bangun Nusantara, 2025)
This study explores the strategic role of local wisdom in village economic development through tourism-based community empowerment programs. Local wisdom is defined as a set of cultural values, norms, and practices that regulate the relationship between communities and their social-ecological environment. These values serve as the foundation for sustainability-oriented village tourism. The research employs a literature study with a Content Analysis approach, focusing on conceptual analysis. Data were obtained from 15 secondary sources, including books and journal articles published between 2021 and 2025, selected through purposive sampling with the assistance of the Publish or Perish application. The findings reveal two key aspects. First, local wisdom functions as the primary identity that enhances destination attractiveness through cultural narratives, traditional attractions, ecological practices, and community ethics. Its integration into tourism enriches visitor experiences, strengthens social cohesion, and supports environmental sustainability. Second, tourism-based empowerment programs generate significant economic impacts, reflected in increased employment, growth of local MSMEs, higher village economic turnover, and improved community capacity in business and tourism management. The involvement of women and youth in creative economy activities further expands inclusivity. Overall, local wisdom emerges not only as cultural heritage but also as an effective instrument for sustainable economic development.